Design and Development of a Guiding Model for the Banking System to Promote Urban Entrepreneurship (Case Study: Shahr Bank Branches in Tehran) - Nasiri , Mohsen; Minouei , Mehrzad; Fathi, Zadollah; Kabaranzad Ghadim, Mohammad Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aims to design a guiding model for the banking system to promote urban entrepreneurship in Shahr Bank branches in Tehran. Methodology: This qualitative study was conducted through the analysis of semi-structured interviews with 16 experts and specialists in banking and entrepreneurship, as well as professors in the fields of entrepreneurship and management. Content analysis of the interviews and research was performed using MaxQda 2020 software to extract the relevant dimensions and codes. The importance and priority of each were determined using the Shannon entropy technique. Findings: Based on the research approach, 3 categories, 37 concepts, and 192 codes were extracted. The mission of Shahr Bank in urban development, the desire of entrepreneurs for financing from the bank, and the facilitation of terms and conditions for granting entrepreneurship loans in the section of causal factors, the profit-oriented approach in the banking system, banking regulations, and strategic weakness in the section of intervening factors, and the induction of a culture of support for entrepreneurship, expansion of Shahr Bank’s scope of activities, and combating poverty and destructive jobs in the section of outcomes gained the highest importance coefficients. Conclusion: In this study, a guiding model for the banking system to promote urban entrepreneurship was presented in three sections: causal factors, intervening factors, and outcomes. Since a comprehensive guiding model for the banking system to promote urban entrepreneurship has not been presented so far, this research can be beneficial in enhancing the role of the banking system in the field of entrepreneurship and the development of cities.